Potential of Bombyx mori fibroin peptide as an inhibitor of BMP2 and TGFB1 in the treatment of pulp tissue damage - Sartika Puspita; Sri Nabawiyati Nurul Makiyah; Masaki Kita; Ahmad Hafidul Ahkam (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Silk from Bombyx mori, a species of silkworm, contains fibroin, which has good biocompatibility and is potentially suitable for medical applications, especially in the treatment of tissue damage. Purpose: This study evaluated the potential interaction of B. mori fibroin peptides with bone morphogenetic protein 2 (BMP2) and transforming growth factor beta 1 (TGFB1), which are protein markers for dentine reparative activity. Methods: The research was carried out in silico. The three-dimensional structure of the proteins was obtained from the Research Collaboratory for Structural Bioinformatics Protein Data Bank (RCSB PDB), and the antimicrobial potential of fibroin was evaluated using Antimicrobial Peptide Scanner v.1, the Collection of Anti-Microbial Peptides (CAMPR3), PeptideRanker, ToxinPred, AlgPred, and AllergenFP. Molecular modeling and analysis were performed with trRosetta, PrankWeb, the HDOCK server, and Discovery Studio. Results: The light chain 1 peptide (LC1), light chain 2 peptide (LC2), heavy chain 2 (HC2), and heavy chain 7 (HC7) showed high binding affinity to BMP2, while LC2, HC1, HC3, and HC6 showed high binding affinity to TGFB1 compared to silicic acid as a standard anti-inflammatory drug. Conclusion: These seven peptides can potentially interact with BMP2 or TGFB1 and might have anti-inflammatory capability.